2008
DOI: 10.3748/wjg.14.5969
|View full text |Cite
|
Sign up to set email alerts
|

Insight into congenital absence of the portal vein: Is it rare?

Abstract: Congenital

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 117 publications
0
44
0
1
Order By: Relevance
“…[89] At 5 weeks gestational age, the right and left vitelline veins forms a branching venous plexus around the duodenum, comprising two components ventral to the duodenum and one component dorsal to the duodenum, before terminating in the sinus venous. By 10 weeks, selective involution of portions of this venous plexus gives rise to the adult portal vein.…”
Section: Discussionmentioning
confidence: 99%
“…[89] At 5 weeks gestational age, the right and left vitelline veins forms a branching venous plexus around the duodenum, comprising two components ventral to the duodenum and one component dorsal to the duodenum, before terminating in the sinus venous. By 10 weeks, selective involution of portions of this venous plexus gives rise to the adult portal vein.…”
Section: Discussionmentioning
confidence: 99%
“…Both males had a single b-HCA transformed in HCC and the female had multiple H-HCA. Focal liver cell lesions including HCA, HCC, focal nodular hyperplasia, and nodular regenerative hyperplasia have been reported in association with congenital absence of the portal vein, also known as congenital extrahepatic portosystemic shunt or Abernethy malformation [5–8, 2527]. It has been suggested that the decreased venous blood flow combined with an increased arterial blood flow could result in abnormal perfusion of the liver and to uneven vascular perfusion of the liver giving rise to a hyperplastic response, and to a spectrum of nodular lesion including HCA [5, 28].…”
Section: Discussionmentioning
confidence: 99%
“…The number of cases of Abernethy syndrome has increased in recent years, due to advances in imaging techniques 2.…”
Section: Introductionmentioning
confidence: 99%